The effects of mindful self-care on medical resident wellness, depression, and burnout - Wendy M. GUYKER; Evette A. ADDAI; Catherine P. COOK-COTTONE; Susan M. ORRANGE; Sofie SCALETTA (Journal of Health and Social Sciences)
Introduction: The Accreditation Council for Graduate Medical Education (ACGME), a U.S. nonprofit organization setting educational standards for safe and high-quality medical care, recently expanded its requirements for resident well-being, emphasizing self-care. However, little research exists on this topic. This study aimed to assess the types and frequency of mindful self-care behaviors, defined as intentional practices that promote awareness of internal needs and external demands. It also examined the relationship between self-care, well-being, burnout, distress, and depression, and whether self-care can protect residents from depression linked to burnout and distress. Methods: A cross-sectional survey was conducted with medical residents at a Northeastern U.S. medical school over three months. Residents in their first four years of surgical and non-surgical specialties received an email with a survey link and informed consent. Mindful self-care was assessed using the Mindful Self-Care Scale (MSCS), distress with the Physician Well-Being Index (PWBI), depression with the Patient Health Questionnaire-9 (PHQ-9), and wellness with the Brief Resident Wellness Profile (BRWP). Data were analyzed using SPSS, with moderation analyses performed to explore self-care’s role in mitigating depression linked to distress. Results: A total of 104 residents participated (15.95% response rate). Self-care positively correlated with resident well-being (r = .62, p < .0001) and negatively correlated with resident distress (r = -.50, p < .0001) and resident depression (r = -.56, p < .0001). Burned-out residents had significantly less self-care than those not burned out (F (1,97) = 15.69, p < .0001). Moderation analyses evidenced that mindful self-care is protective for residents against developing depression related to burnout and distress. Discussion: This research shows that resident self-care is strongly linked to well-being and is associated with lower distress, depression, and burnout. It highlights that self-care can protect against poor health outcomes during residency and emphasizes that self-care can involve changing one’s approach rather than requiring additional resources like time or money.